AT OVERGIVE SIG TIL, ELLER MANIPULERE, MED SKÆBNEN? Drømmevarsler og hverdagsmagi i Kirgistan - Louw, Maria (Tidsskriftet Antropologi, 2010)
In Kyrgyzstan dreams are of great significance as sources of omens and divine revelations. In the practice of dream interpretation a complex relationship between belief in fate and belief in the free will is expressed: Through magical practices which manipulate dream omens people sometimes seek to effect what is about to happen, changing the fate that they, in other situations, claim not to have any control of. It is argued that dream omens embody peoples hopes for, and fears about, how their lives may develop. Through their interpretation of the omens and through the magical acts with which they often handle them, they enter a virtual realm where they and people who are close to them can imagine and orient themselves toward possible future scenarios and test their social resonance. With the interpretation of, and magical manipulation with, omens, a person’s fate becomes a social riddle which concerns not only the directions her life might, or ought to, take, but also the question of what she can do herself in order to bring a desired future about herself, and what she should leave in the hands of fate. Keywords: Kyrgyzstan, dreams, magic, omens, transition, Islam